2023
DOI: 10.1039/d2en00574c
|View full text |Cite
|
Sign up to set email alerts
|

Light-nutrition coupling effect of degradable fluorescent carbon dots on lettuce

Abstract: The increasing application of carbon dots (CDs) inevitably lead to environmental leakage. To be environmentally friendly, degradable CDs will be the mainstream on agricultural application in the future. Our study...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…These results suggest that Ce-CDs can carry electrons and accelerate the electron transfer rate. Consequently, Ce-CDs can promote the formation of photosynthetic products by significantly increasing the ETR 29 and qP, which further improves the light energy utilization efficiency of PS II and enhances the photochemical energy conversion efficiency [Y(II)]. 63 Besides, Ce-CDs in chloroplasts can absorb UV light and emit blue fluorescence.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest that Ce-CDs can carry electrons and accelerate the electron transfer rate. Consequently, Ce-CDs can promote the formation of photosynthetic products by significantly increasing the ETR 29 and qP, which further improves the light energy utilization efficiency of PS II and enhances the photochemical energy conversion efficiency [Y(II)]. 63 Besides, Ce-CDs in chloroplasts can absorb UV light and emit blue fluorescence.…”
Section: Resultsmentioning
confidence: 99%
“…23 Many studies have shown that CDs have great potential in promoting plant growth, such as promoting growth and development, regulating plant photosynthesis, and improving plant stress resistance. 24–29 Kou et al have discovered that the activation of aquaporin-encoding genes by CDs can expedite seed germination, stimulate roots and hypocotyl elongation in seedlings, and enhance mineral element absorption and photosynthesis to improve both yield and nutritional quality in mature plants. 30 Tan et al have found that 100 mg L −1 N-CDs increased the chlorophyll a content by 12.68%, electron transport rate by 38.61%, and Rubisco activity by 60.61%, which significantly promoted the biomass accumulation (41.70%) and increased the nutrient content of lettuce.…”
Section: Introductionmentioning
confidence: 99%
“…Chloroplast suspensions were extracted as defined by Pan et al 24 and the chlorophyll concentration was 360 mg L −1 . Chloroplast suspensions were mixed with 10, 100, 250, and 500 mg L −1 TiO 2 NPs (1 : 1), respectively, and incubated in the dark for 2 h to obtain TiO 2 and chloroplast complexes (TiO 2 / Chl).…”
Section: Hill Reaction and Optical Property Monitoringmentioning
confidence: 99%
“…Thus, its impact on the environment is negligible. Furthermore, CDs can accelerate the photosynthesis process in plants [18,19]. These advantages make CDs promising green fertilizers for plants.…”
Section: Introductionmentioning
confidence: 99%